Theoretical Predictions for Sociogenomic Data: The Effects of Kin Selection and Sex-Limited Expression on the Evolution of Social Insect Genomes - Linksvayer, Timothy A.; Wade, Michael J. (Frontiers in Ecology and Evolution, 2016)
Kin selection theory has always been explicitly genetic and has long been invoked to explain the evolution of the sterile worker caste in the social insects. However, sociogenomic studies of the evolution and genomic basis of social insect caste have been largely disconnected from kin selection theory and other related genetic theories of social evolution. Two previous population genetic models make testable predictions for patterns of sequence diversity for genes shaped indirectly by kin selection compared to genes shaped directly by natural selection, but there is some confusion in the literature regarding the predicted effects of kin selection and sex-limited expression on molecular evolution. We review the previous models and then use a simple parental effect model to clarify that the two factors, kin selection and sex-limited expression, are distinct and each has a separate effect on the expected patterns of molecular evolution. We further build on the previous models to show how categories of genes in social insect genomes with diverse combinations of fitness effects (direct, parental, sib, and offspring) and patterns of sex-limitation are predicted to evolve. We discuss how caste- and sex-specific transcriptomic profiling, coupled with population genomic data, can be used to identify different functional categories of genes and subsequently test whether observed patterns of molecular evolution fit theoretical predictions.